Leaders of Men: Ten Marines Who Changed the Corps - Venzon, Anne Cipriano (Rowman & Littlefield Publishers, 2008)
What was it that transformed the United States Marine Corps from a quasi-constabulary in 1861 to one of the world's elite fighting forces by 1918? As there was nothing terribly unusual about the Corps' organization or bureaucracy, the only conclusion left is that it must have been its extraordinary people. The Civil War attracted to the USMC a handful of young men who were natural leaders. These men then trained another cohort of talented, tenacious leaders, who, in turn, molded the men who led the Marine Corps into the twentieth century. Many of their names have faded in the brighter lights of the campaigns in the Pacific, Korea, and Vietnam, but without men like Huntington, Cochrane, and Myers, there wouldn't have been Puller, Edson, or Pace in later years. Author Anne Cipriano Venzon selected ten men whose skills and leadership clearly contributed to the formation of the ethos, which became the modern Marine Corps. By examining each man's strengths and weaknesses, the continuum of leadership from the earliest days of the Corps becomes very clear for the reader. Based on extensive research, most of it in little-used primary documents, the biographies of the ten men featured in Leaders of Men look both at the men and their role in various engagements and events. From Lincoln's Gettysburg Address and the search for the Alabama during the Civil War to the Battle of Belleau Wood and "peacekeeping" missions in China in the 1920s, the examination of these careers will give readers a better understanding of what it means to be a Marine.